2019
DOI: 10.1111/1556-4029.14207
|View full text |Cite
|
Sign up to set email alerts
|

Mouth Width and Cupid’s Bow Estimation in a Southern African Population

Abstract: Standards for estimating mouth width and Cupid’s bow width in craniofacial approximation and superimposition are limited. Currently, the only guideline for mouth width, using direct skeletal references, is a general rule indicating a 75% inter‐canine to mouth width ratio. The philtrum, which closely corresponds to the Cupid’s bow, is said to be equal to the inter‐superior prominences of the maxillary central incisors. This study tested these guidelines against newly generated regression models and mean values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Using geometric morphometrics, it was found that age significantly (p < 0.0001) impacted mouth morphology, affecting all population and sex groups in a similar way (Fig 2). This study delivered a unique wireframe visual that demonstrates the impact of age on soft and hard tissue mouth shape, which is largely consistent with metric descriptions previously reported by authors [14,[18][19][20]23,24,[36][37][38]. The identified age-related lip-thinning, reduction in teeth height, and increase in mouth width, are well recognised in published literature [14,[18][19][20][36][37][38].…”
Section: Plos Onesupporting
confidence: 87%
See 4 more Smart Citations
“…Using geometric morphometrics, it was found that age significantly (p < 0.0001) impacted mouth morphology, affecting all population and sex groups in a similar way (Fig 2). This study delivered a unique wireframe visual that demonstrates the impact of age on soft and hard tissue mouth shape, which is largely consistent with metric descriptions previously reported by authors [14,[18][19][20]23,24,[36][37][38]. The identified age-related lip-thinning, reduction in teeth height, and increase in mouth width, are well recognised in published literature [14,[18][19][20][36][37][38].…”
Section: Plos Onesupporting
confidence: 87%
“…These results more closely correspond to this study (males = 56.2 mm, SD 4.8; females = 53.7 mm, SD 4.6). All these findings consequently suggest that population specific regression [i.e., 20,23,24], supported by the morphometric guides generated in this study, are currently needed to assist with mouth approximation.…”
Section: Plos Onementioning
confidence: 66%
See 3 more Smart Citations